Growth of flower-like patterns of TiO2 nanorods over FTO substrate - Issar, Sheetal; Poddar, Pankaj; Mehra, N. C.; Mahapatro, Ajit K. (International Conference on Technologically Advanced Materials (ICTAM), 2017)
Nanostructures such as nanoparticles, nanowires, nanorods, nanotubes have attracted great interest with the understanding of shape and size dependence in the electronic and sensing properties. This work demonstrates growth and characterization of one-dimensional nanorods of titanium-dioxide (TiO2) on the fluorine doped tin oxide (FTO) substrate by using hydrothermal method. Field effect scanning electron microscopy shows flower-like morphology, and energy-dispersive X-ray spectroscopy confirms the presence of Ti and O. The X-ray diffraction peaks agree well with the JCPDS data. Initially, the 1D nanorods are formed and high concentration of precursor assists evolution of the short branches to form flower-like structures.